Changes of Quality Characteristics before and after Embrittlement of Oreochromis niloticus×O. aureus - Mei CHEN; Jingkai QIN; Ziyi YANG; Zhongyi QIN; Jie ZHOU; Jiequn JIANG; Xiaoling LIU (Shipin gongye ke-ji)
Oreochromis niloticus×O. aureus was taken as the research object, and the difference of nutrient composition, thermodynamic property, microstructure, texture property and sensory quality between normal tilapia (NT) and crisp tilapia (CT) was analyzed to find out the effective development and utilization direction of brittle tilapia. The results showed that the moisture content of CT was significantly lower than that of NT (P<0.05), but the protein and fat content of CT were 14.99% and 61.48% higher than that of NT, respectively. Compared with NT, the contents of total amino acid, essential amino acid and umami amino acid were significantly increased (P<0.05), and the contents of myofibrillar protein, matrix protein and collagen were increased by 10.77%, 8.65% and 51.15%, respectively. A total of 19 fatty acids were detected by CT, and the ratio of saturated fatty acids:monounsaturated fatty acids:polyunsaturated fatty acids was 1.63:1.20:1. The freezing point of CT was −0.81℃, lower than that of NT was −0.73 ℃, and the enthalpy of protein denaturation was 21.48% higher than that of NT. The muscle fiber structure of CT was more compact and dense, and the hardness, stickiness and mastication of CT were significantly higher than those of NT (P<0.05). The overall sensory quality of fish was improved by 23.84% after embrittlement. The results showed that after embrittlement, the muscle composition and quality indexes changed to different degrees, which was the key factor to improve the nutritional value and meat quality of the fish. In summary, CT not only shows significant advantages in nutritional value, but also superior to NT in texture characteristics and sensory texture, which provided a scientific basis for processing and marketing of crisp meat tilapia.